Embracing sustainability in public-owned forest resources management: Lessons learned and perspectives - Boukherroub, Tasseda; Ruiz, Angel (Frontiers in Sustainability, 2023)
The growing interest in sustainability has pushed governments to the elaboration of new legislations and orientations and, in turn, has led companies and organizations to consider sustainability goals in their strategies, operations management, and decision-making processes. This is the case in natural resources supply chains, and particularly in forest products supply chains, where the row resource is publicly owned but exploited by private companies. While public owners are responsible of the sustainable management of the resource according to the three sustainability pillars, industrials tend to focus on the use of the allocated resources to maximize their utility, mainly from an economic perspective. The key question is how to rethink the whole public owners – industrials relationship to ensure consensual and satisfactory solutions for all the stakeholders. In this context, this paper reviews and analyzes sustainable supply chain planning approaches proposed in the forestry planning literature and, based on the model observed in the forestry sector in the province of Quebec, Canada, proposes and analyzes a new approach to overcome its challenges and facilitate sustainability integration in the forestry planning processes.